Hadith Educational Media: Learning During the Time of the Prophet and Its Relevance in the Contemporary Era - Tutia Rahmi; Rahmi Syahriza; Asrar Mabrur Faza (Kasyafa: Jurnal Pendidikan Agama Islam, 2025)
Education is a basic need of society. So that learning methods of course follow developments over time, including the education system, implementation and media used, this research focuses on hadith educational media and their relavance in the contemporary era. With the aim of making it easier for people to understand hadith contextually and correlatively in the contemporary era, hadith is increasingly developing rapidly. This research uses qualitative methods, namely focusing on the process of drawing comparative conclusions and examining the dynamics and relationships between events through the application of scientific reasoning. Then this research focuses on learning media in the time of the Prophet and reviews the correlation in the contemporary era. The research results show that the correlation of the hadith of the Prophet Muhammad, which was narrated by several Imams, interprets several types of hadith educational media and confirms the relevance of educational media in the dimensions of the hadith of the Prophet Muhammad. The various media in question consist of the Prophet's way of conveying hadiths, the practices that the Prophet carried out include signals that the Prophet gave when someone asked about slaughtering during the Hajj, so if it is correlated with today's era, namely the use of emoticons that make things easier for society.